Improving Concentration Ability Through Rainbow Card Media For Children Age 4 – 5 Years In Kindergarten - Siti Sumiani; Agus Salim; Choirun Nisak Aulina (Indonesian Journal of Islamic Studies, 2018)
Concentration ability is the ability possessed by every child to focus and focus on doing or doing something. Based on research at the Roudhotul Anwar Sukodono Islamic Kindergarten, especially in the 4-5 year age group, 80% of children lack the ability to concentrate. Researchers have a good target of successful concentration power is 76%-100%, for that researchers use Rainbow Card media to improve children's concentration skills. has never been carried out before to improve the process of teaching and learning activities so that student learning outcomes increase. The class action uses 2 stages, namely pre-cycle and cycle I. In the pre-cycle activity, storytelling is applied and the results have not yet reached the target of success, with a total of 40.4%. In the first cycle activities implemented Rainbow Card activities and achieved the success target with a total of 80%. This shows that from the increase in the percentage of the average pre-cycle and cycle I, there has been a very good increase, so that this study can be judged to have met the specified success target, the results of the study in group A in Islamic Kindergarten Roudhotul Anwar were declared successful, this proves that the media Rainbow Card can improve the concentration ability of children aged 4-5 years at Islamic Kindergarten Roudhotul Anwar Sokodono.